Pengaruh Problem Solving Therapy terhadap Kecemasan Global pada Pasien Skizofrenia - Nafiah, Putri Nur Hidayatun; Untari, Rita (Politeknik Kesehatan Kemenkes Surakarta, 2024)
Background: Schizophrenia is a serious mental disorder that is often encountered and hospitalized. Schizophrenia is a long-term and serious brain disease that results in psychotic behavior, concrete thinking, and difficulties in processing information, interpersonal relationships, and solving problems. One of the symptoms that arise from various types of disorders and symptoms of schizophrenia is anxiety which affects daily functional limitations, including the inability to solve problems. Therefore, non-pharmacological therapy with CBT is given to train the patient's problem-solving skills. Objectives: This study aims to determine the effect of problem-solving therapy on global anxiety in schizophrenia patients. Methods: This research uses a quantitative approach, with a pre-experimental research design type One group Pretest-posttest. The research sample consisted of 22 people, obtained through purposive sampling. The instrument used to measure the sample's anxiety was the Hamilton Anxiety Rating Scale (HARS). Hypothesis testing analysis uses a paired sample t-test. Results: The research sample was dominated by men (63.6%), aged 26-35 years (50%), had a history of high school/K education (50%), and a low socioeconomic level (81.8%). Hypothesis testing showed a p-value of 0.000 (p<0.05). Conclusion: Problem-solving therapy affects the global anxiety of schizophrenia patients at RSJD Dr. RM. Soedjarwadi Klaten. Bibliography: 74 (2009-2023) Keywords: Problem-Solving Therapy, Anxiety, Schizophrenia